1988
DOI: 10.1111/j.1365-2044.1988.tb09066.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propofol on cerebrospinal fluid pressure and cerebral perfusion pressure in patients undergoing craniotomy

Abstract: The effects of propofol on cerebrospinal fluid pressure, mean arterial pressure, cerebral perfusion pressure and heart rate were studied during induction, tracheal intubation and skin incision in 23 patients scheduled for elective craniotomy. Premedication consisted of midazolam 0.1 mg/kg intramuscularly and metoprolol 1 mg/kg orally. Measurements were made or derived at time zero and 0.5, 1, 1.5, 2 and 3 minutes after an induction dose of propofol 1.5 mg/kg. A continuous infusion of propofol was started at ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(35 citation statements)
references
References 20 publications
3
30
0
2
Order By: Relevance
“…The dif ferences between the two studies may be due to technical differences; the previous study used only 6.0 patients who received diprivan over 90 s and ICP was measured using an intraventricular pressure monitor. In patients undergoing intracranial surgery (for aneu rysm or tumours) ICP was reduced after in duction of anaesthesia with diprivan 1.5 mg/ kg [5] and 0.35 and 0.8 mg/kg [6], which agrees with our results. The fact that Ravussin et al [5] reported no significant change in CPP may arise because they measured cere brospinal fluid (CSF) pressure as a measure of ICP which can be inaccurate.…”
Section: Discussionsupporting
confidence: 83%
“…The dif ferences between the two studies may be due to technical differences; the previous study used only 6.0 patients who received diprivan over 90 s and ICP was measured using an intraventricular pressure monitor. In patients undergoing intracranial surgery (for aneu rysm or tumours) ICP was reduced after in duction of anaesthesia with diprivan 1.5 mg/ kg [5] and 0.35 and 0.8 mg/kg [6], which agrees with our results. The fact that Ravussin et al [5] reported no significant change in CPP may arise because they measured cere brospinal fluid (CSF) pressure as a measure of ICP which can be inaccurate.…”
Section: Discussionsupporting
confidence: 83%
“…MAP and intracranial pressure (ICP) are both parameters required to calculate the CPP (CPP = MAP -ICP). In a study by Ravussin et al [17], a significant decrease in ICP was noted after propofol induction. The fall in MAP in our study may have counted towards a decrease in CPP and contributed to further cortical depression.…”
Section: Resultsmentioning
confidence: 90%
“…56 '57 Stephan et al 57 observed average CBF and CMR decreases of 51 and 36 per cent respectively after administration of propofol by bolus plus infusion (2 mg.kg -I and 0.2 mg.kg-t.min-~). Ravussin et al 58 measured lumbar CSF pressure during induction of anaesthesia by slow bolus administration of propofol (I.5 mg-kg -~ over 30 sec) in patients about to undergo craniotomies. They reported mean maximum reductions in lumbar CSFP and CPP of 32 and 10 per cent respectively.…”
Section: Propofolmentioning
confidence: 99%